A Comparison of Molecular Biology Mechanism of Shewanella putrefaciens between Fresh and Terrestrial Sewage Wastewater - Xu, Jiajie; He, Weina; Wang, Zhonghua; Zhang, Dijun; Sun, Jing; Zhou, Jun; Li, Yanyan; Su, Xiurong (Frontiers in Bioengineering and Biotechnology, 2016)
Municipal and industrial wastewater is often discharged into the environment without appropriate treatment, especially in developing countries. As a result, many rivers and oceans are contaminated. It is urgent to control and administer treatments to these contaminated rivers and oceans. However, most mechanisms of bacterial colonization in contaminated rivers and oceans were unknown, especially in sewage outlets. We found Shewanella putrefaciens to be the primary bacteria in the terrestrial sewage wastewater outlets around Ningbo City, China. Therefore, in this study, we applied a combination of differential proteomics, metabolomics, and real-time fluorescent quantitative PCR techniques to identify bacteria intracellular metabolites. We found S. putrefaciens had 12 different proteins differentially expressed in freshwater culture than when grown in wastewater, referring to the formation of biological membranes (Omp35, OmpW), energy metabolism (SOD, deoxyribose-phosphate pyrophosphokinase), fatty acid metabolism (beta-ketoacyl synthase), secondary metabolism, TCA cycle, lysine degradation (2-oxoglutarate reductase), and propionic acid metabolism (succinyl coenzyme A synthetase). The sequences of these 12 differentially expressed proteins were aligned with sequences downloaded from NCBI. There are also 27 differentially concentrated metabolites detected by NMR, including alcohols (ethanol, isopropanol), amines (dimethylamine, ethanolamine), amino acids (alanine, leucine), amine compounds (bilinerurine), nucleic acid compounds (nucleosides, inosines), organic acids (formate, acetate). Formate and ethanolamine show significant difference between the two environments and are possibly involved in energy metabolism, glycerophospholipid and ether lipids metabolism to provide energy supply and material basis for engraftment in sewage. Because understanding S. putrefaciens’s biological mechanism of colonization (protein, gene express and metabolites) in terrestrial sewage outlets is so important to administering and improving contaminated river and to predicting and steering performance, we delved into the biological mechanism that sheds light on the effect of environmental conditions on metabolic pathways.